2023
DOI: 10.3724/abbs.2023241
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell exosomes inhibit nucleus pulposus cell apoptosis via the miR-125b-5p/TRAF6/NF-κB pathway axis

Yang Duan,
Cheng Yu,
Wenhao Kuang
et al.

Abstract: Intervertebral disc degeneration (IVDD) is the pathological basis of a range of degenerative spinal diseases and is the primary cause of lower back pain. Mesenchymal stem cell (MSC) transplantation inhibits IVDD progression. However, the specific mechanisms that underlie these effects remain unclear. In this study, candidate microRNAs (miRNAs) are screened using bioinformatics and high-throughput sequencing. TNF-α is used to induce nucleus pulposus cell (NPC) degeneration. MSC-derived exosomes (MSC-exosomes) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Additionally, the regulatory measures and ethical concerns associated with cell therapy products derived from human sources pose significant challenges, consuming a substantial amount of time. Numerous studies have suggested that cell therapy achieves therapeutic effects by activating pathways through paracrine signaling molecules ( Duan et al., 2023 ; Zhou et al., 2023 ). Consequently, extracellular vesicles (EVs) have emerged as a new focal point of research.…”
Section: Treatment Of Aseptic Inflammationmentioning
confidence: 99%
“…Additionally, the regulatory measures and ethical concerns associated with cell therapy products derived from human sources pose significant challenges, consuming a substantial amount of time. Numerous studies have suggested that cell therapy achieves therapeutic effects by activating pathways through paracrine signaling molecules ( Duan et al., 2023 ; Zhou et al., 2023 ). Consequently, extracellular vesicles (EVs) have emerged as a new focal point of research.…”
Section: Treatment Of Aseptic Inflammationmentioning
confidence: 99%
“…Several reports on reversing IDD have been published, such as related studies on exosomes [ 15 17 ] and some examples of new classical drugs, including metformin [18] and dexamethasone [19] . However, at present, the main treatment for IDD is still limited to relieving symptoms, which cannot solve the fundamental problem of disc degeneration [20] .…”
Section: Introductionmentioning
confidence: 99%